Role of the federal Sharia court in the elimination of interest from Pakistan’s economy - Ullah, Niamat; Baz Muhammad , Prof. Dr. Sahibzada; Baloch, Fehmida (Journal of Quranic and Social Studies, 2023)
The Islamic Republic of Pakistan, whose constitution binds all institutions to the revival of the Islamic system, follows a 20-year legal battle by the Federal Sharia Court to rid the country of usurious economy and the recent decision to abolish usury by 2022. It has entered the next phase in which judicial, constitutional, administrative and interest barriers are in place, which require concerted and serious efforts to overcome. Instead of getting entangled in legal gimmicks and tricks during the five-year grace period given by the Federal Shariat Court, according to the correct Islamic thought and leadership, the government and related institutions will not repeat the mistake that was made in the 90s and which resulted in financial and They are still suffering in the form of economic difficulties. Therefore, the elimination of interest from the economic system of Pakistan is very necessary so that the inhabitants of this Muslim country can achieve the goals of establishing their state.